2008
DOI: 10.1080/08880010802313509
|View full text |Cite
|
Sign up to set email alerts
|

PRENATAL DIAGNOSIS OF β-THALASSEMIA IN EGYPT: Implementing Accurate High-Tech Methods Did not Reflect Much on the Outcome

Abstract: The clinical severity of thalassemia major makes it a priority genetic disease for prevention programs through prenatal diagnosis for carrier couples. Incorporation of automated DNA sequencing that enables the characterization of mutations not detected by other mutation specific detection procedures was a prime goal of this work. Automated DNA sequencing was offered on fetal tissues in 30 pregnancies during the year 2005. The pregnancies were at high risk for homozygosity or compound heterozygosity for beta-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In a previous report from Egypt, only 36% of pregnant mothers with affected fetuses elected to terminate their pregnancy despite being counseled about the hazards of having an affected child and the often poor prognosis in Egypt. These couples were well aware of the complications of thalassaemia major as they already had at least one affected live child …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous report from Egypt, only 36% of pregnant mothers with affected fetuses elected to terminate their pregnancy despite being counseled about the hazards of having an affected child and the often poor prognosis in Egypt. These couples were well aware of the complications of thalassaemia major as they already had at least one affected live child …”
Section: Discussionmentioning
confidence: 99%
“…Educational programs for the patients and their parents have been conducted on a limited scale . Although prenatal diagnosis of β‐thalassaemia has been previously conducted in Egypt in at‐risk pregnancies, the majority of the couples continued the affected pregnancy despite knowledge of the hazards of an affected child in Egypt …”
Section: Introductionmentioning
confidence: 99%
“…The mean gestation period at the time of PND was 14 (10-18) weeks. All mothers had a previous affected pregnancy, and 13 had two or more previous affected pregnancies (Elgawhary et al 2008). On the other hand, a more recent study presenting the current status of the PND services and results from the largest thalassaemia centre in Egypt treating 3,000 patients showed that all 24 women who underwent prenatal testing and received a diagnosis that the foetus is affected by β-thalassemia major opted for pregnancy termination.…”
Section: Prenatal Genetic Diagnosis For Haemoglobinopathies In Arab Cmentioning
confidence: 99%
“…The almost universal choice to terminate by the couples with affected fetuses is consistent with that reported from many countries, 26,30,[32][33][34] with rare exceptions. 35 Improvements to our programme are still needed, including establishing better contact with the couples at risk (with periodic follow up), improving the genetic counselling to ensure a higher uptake of PND, upgrading and intensifying the population education programmes, offering voluntary haemoglobinopathy screening to couples married prior to 2008, and establishing better awareness among the thalassaemic families of the value of PND to prevent the birth of further affected children.…”
Section: Ivs-i-mentioning
confidence: 99%